Peningkatan Kualitas Hidup Lansia Untuk Pemberdayaan Masyarakat di Kelurahan Mangga Dua Lingkungan III Kecamatan Padan Tahun 2023 - Emelia Apriani Tampubolon; Rizky Andriani Bakara (Indonesian Journal Publisher, 2023)
The elderly are an age group in humans who have entered the final stage of the life phase. The existence of old age is characterized by life expectancy which is increasing from year to year, it requires efforts to maintain and improve health to be able to achieve a healthy, happy, empowered, and productive old age. Quality is a measuring tool to assess the success of a health service action in addition to morbidity, mortality, fertilization, and disability. This quality of life should be considered by health professionals so that it can be a reference for the success of an intervention or therapy. The subjects in the service activities were elderly people aged over 60 years in Neighborhood III, Mangga Dua Village, Pandan District, as many as 15 people. In the initial stage, an approach was made to residents to deliver counseling material using the lecture method and continued with a question and answer session and gymnastics with the elderly. Community service activities were carried out on Friday, March 31, 2023 at 09.00 WIB until completion. When the activity began, residents arrived to register, then heard the material presented and the elderly were invited to follow the elderly gymnastics. It is hoped that elderly parents will be more productive, active, healthy, resilient and protected, in order to improve the quality of life of the elderly.